Pediatric Collections: Social Determinants of Health: Part 2: Effects of Inequity 2022
DOI: 10.1542/9781610026376-part02-discrimination
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Subsequent Mental Health, Substance Use, and Well-being in Young Adults

Abstract: OBJECTIVES: Discrimination has been shown to have profound negative effects on mental and behavioral health and may influence these outcomes early in adulthood. We aimed to examine short-term, long-term, and cumulative associations between different types of interpersonal discrimination (eg, racism, sexism, ageism, and physical appearance discrimination) and mental health, substance use, and well-being for young adults in a longitudinal nationally representative US sample. METHODS:We used data from 6 waves of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Additionally, extensive evidence documents the role of racism and daily discrimination experienced by Hispanics, African Americans and other ethnic minorities (Williams et al, 2003), with research finding associations with poor psychological and physical health outcomes among adolescents (Huynh & Fuligni, 2010; Sirin et al, 2015) and emerging adults (Cano, Schwartz, et al, 2021). We found that a higher frequency of everyday discrimination was related to 7% lower odds of flourishing, even when controlling for demographic characteristics, adolescent flourishing and multiple indicators of healthy development, which support Lei et al's recent findings (2021). The relationship between Hispanic/Latino ethnicity, everyday discrimination and flourishing warrants further exploration, particularly given the relationship others have found between ethnic discrimination and mental health disorders among Hispanic emerging adults (Cano, Schwartz, et al, 2021).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, extensive evidence documents the role of racism and daily discrimination experienced by Hispanics, African Americans and other ethnic minorities (Williams et al, 2003), with research finding associations with poor psychological and physical health outcomes among adolescents (Huynh & Fuligni, 2010; Sirin et al, 2015) and emerging adults (Cano, Schwartz, et al, 2021). We found that a higher frequency of everyday discrimination was related to 7% lower odds of flourishing, even when controlling for demographic characteristics, adolescent flourishing and multiple indicators of healthy development, which support Lei et al's recent findings (2021). The relationship between Hispanic/Latino ethnicity, everyday discrimination and flourishing warrants further exploration, particularly given the relationship others have found between ethnic discrimination and mental health disorders among Hispanic emerging adults (Cano, Schwartz, et al, 2021).…”
Section: Resultssupporting
confidence: 89%
“…Racialized group status might also be related to flourishing. Evidence indicates that chronic exposure to frequent interpersonal and systemic stressors puts Hispanic or Latino, Black or African American and members of other racially minoritized groups at higher risk of poor mental health such as depression (Huynh & Fuligni, 2010; Sirin et al, 2015; Williams et al, 2003), and findings from a recent study indicates that higher frequency of everyday discrimination is related to lower odds of flourishing (Lei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation